A review on Rhodococcus equi: horse, cat and human - Aslam, Muhammad Waseem; Lau, Seng Fong (Veterinary Association Malaysia, 2019)
In recent years, Rhodococcus equi has emerged as pathogen of importance in respiratory and non-respiratory infectious diseases of animals and humans. Its distribution is worldwide and incidence of disease is increasing in non-equine species like cats and humans. Sporadic infection in human and cat is hypothesized to infect immunocompromised cases largely. While predominantly in foals, infection is quite endemic/epidemic in nature depending on virulence of strain, and incidence is 10 – 20% since birth till weaning. Mode of acquisition is quite variable in humans, cats and foals and depends on the route of exposure. Pathogenesis is well understood in natural host but in cats and humans it is still in its infancy because of the manifestation of unusual cases with low to no exposure to contaminated elements. Clinical signs depend on the site of infection but respiratory manifestations are quite common in foals and human cases. In cats extra-pulmonary disorders are hypothesized as more common presentation. Definitive diagnosis is based on the microbiological culture and cytology from tracheobronchial aspirate for respiratory cases and site of sample for non-respiratory lesions. White blood cells and fibrinogen have some correlation in degree of diagnosis in foals but not in cats and humans. Macrolides especially clarithromycin along with rifampin are considered best combination at the moment and recently resistance is being reported against erythromycin and rifampin. In foals, consensus statements by ACVIM published detailed control and preventions but in humans and cats so far hygiene and isolation of infected patients are for the time being the methods to control nosocomial spread.